Weak state and strong society: An exploration of extortion among Chinese immigrants in Argentina - Li, Jiameng (2016)
Amid Chinese-owned supermarkets in Argentina there are problems of extortion exerted by Chinese criminal groups.A large number of Chinese businessmen have been hit by such extortion activities and some have even suffered from extortionrelated violence, with forty Chinese shopkeepers murdered. This not only poses a challenge to Argentinian authorities that are under pressure to combat the crime but can also have troubling implications for Argentine-Chinese relations.The essay aims to explore how such extortion is carried out in Argentina, and also the reasons behind this organised crime. It first looks at the history of Chinese migration to Argentina. Then it examines the fact of such extortion through the framework of Extortion Racket Systems, including who the criminals are and how they operate within the Chinese community in Argentina.The last part deals with the factors leading to the extortion by using the theory of State in Society.Through the analysis, we can see that such extortion can be seen as a consequence of the interplay between Argentina’s state weakness and the Chinese community’s lack of integration and some cultural issues.